Noncontrast‐enhanced three‐dimensional (3D) intracranial MR angiography using pseudocontinuous arterial spin labeling and accelerated 3D radial acquisition. Issue 3 (24th April 2012) - Wu, Huimin; Block, Walter F.; Turski, Patrick A.; Mistretta, Charles A.; Johnson, Kevin M.
Abstract Pseudocontinuous arterial spin labeling (PCASL) can be used to generate noncontrast magnetic resonance angiograms of the cerebrovascular structures. Previously described PCASL‐based angiography techniques were limited to two‐dimensional projection images or relatively low‐resolution three‐dimensional (3D) imaging due to long acquisition time. This work proposes a new PCASL‐based 3D magnetic resonance angiography method that uses an accelerated 3D radial acquisition technique (VIPR, spoiled gradient echo) as the readout. Benefiting from the sparsity provided by PCASL and noise‐like artifacts of VIPR, this new method is able to obtain submillimeter 3D isotropic resolution and whole head coverage with a 8‐min scan. Intracranial angiography feasibility studies in healthy (N = 5) and diseased (N = 5) subjects show reduced saturation artifacts in PCASL‐VIPR compared with a standard time‐of‐flight protocol. These initial results show great promise for PCASL‐VIPR for static, dynamic, and vessel selective 3D intracranial angiography. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.